2021
DOI: 10.1021/acs.orglett.0c04168
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidative Iridium-Catalyzed Regioselective Annulation of Benzoic Acids with Internal Alkynes

Abstract: Electrochemically driven, Cp*Ir­(III)-catalyzed regioselective annulative couplings of benzoic acids with alkynes have been established herein. The combination of iridium catalyst and electricity not only circumvents the need for stoichiometric amount of chemical oxidant, but also ensures broad reaction compatibility with a wide array of sterically and electronically diverse substrates. This electrochemical approach represents a sustainable strategy as an ideal alternative and supplement to the oxidative annul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 67 publications
0
12
0
2
Order By: Relevance
“…Using the same catalyst precursor, the Mei group achieved electrochemical Ir-catalyzed vinylic C-H functionalization (Figure 12c) 83 and regioselective annulation of benzoic acids with internal alkynes (Figure 12d). 84 In addition, Shi and co-workers reported a method for Ir-catalyzed electrochemical aryl C-H alkynylation reactions (Figure 12e). 85 Gold is highly stable, with a remarkably high E Au+/Au value of 1.8 V vs SHE; and Shi and coworkers found that their attempts to achieve Au-catalyzed electrochemical cross-coupling of terminal alkynes were hampered by cathodic decomposition of the Au catalyst.…”
Section: Electrochemical Noble-transition-metal Catalysismentioning
confidence: 99%
“…Using the same catalyst precursor, the Mei group achieved electrochemical Ir-catalyzed vinylic C-H functionalization (Figure 12c) 83 and regioselective annulation of benzoic acids with internal alkynes (Figure 12d). 84 In addition, Shi and co-workers reported a method for Ir-catalyzed electrochemical aryl C-H alkynylation reactions (Figure 12e). 85 Gold is highly stable, with a remarkably high E Au+/Au value of 1.8 V vs SHE; and Shi and coworkers found that their attempts to achieve Au-catalyzed electrochemical cross-coupling of terminal alkynes were hampered by cathodic decomposition of the Au catalyst.…”
Section: Electrochemical Noble-transition-metal Catalysismentioning
confidence: 99%
“… A and B) Ir‐catalyzed C−H activation of benzoic acids with Ag [57, 58] . C and D) Electrochemical C−H activation of benzoic acids [59, 60] …”
Section: Silver As Oxidantmentioning
confidence: 99%
“…The electrochemical recycling was performed in an undivided cell and the corresponding products 32 a – d were obtained with an outstanding efficiency. In 2021, Mei and Guo expanded the electrochemical method to benzoic acid derivatives with the same reaction conditions (Scheme 13D) [60] . Carboxylate additives proved critical for the transformation.…”
Section: Silver As Oxidantmentioning
confidence: 99%
“…The pentamethylcyclopentadienyl iridium dichloride (Cp*IrCl 2 ) 2 dimer catalyzed electrochemical 4+2 annulation of benzoic acid and alkynes in an undivided cell containing platinum electrodes using tetrabutylammonium acetate in methanol (Scheme 50). [109] The reaction begins with the reaction or iridium catalyst with tetrabutylammonium acetate to form iridium (III) complex. This complex undergoes reaction with benzoic acid through C−H activation and methanol to afford iridacycle.…”
Section: Intermolecular and Intramolecular Cyclizationmentioning
confidence: 99%